Rozwiąż równania. Zrobiłem to sam,ale chcę się sprawdzić ;)

3 (x - 1) + 2 = 8

2 (13 - x) - 9 = 1

3 (1 - x) + 2 = -7

3 (x + 3) = 2 (x + 4) + 1 + x

4 (3x + 2) + 5 (2x + 3) = - (2x + 13)

4 (x - 2) - 2 (x - 4) = 5(x + 1) - 3x

2 (x - 4) = 2 (2x - 1) + 6 (x + 1)

0,2x + 0,3 = 1,3

5x - 0,8 = 0,1 + 2x

½y + 3 = 7

0,6y + 0,4y = 4



1

Odpowiedzi

2010-03-14T14:20:04+01:00
3 (x - 1) + 2 = 8
3x - 3 + 2 = 8
3x - 1 = 8 | + 1
3x = 9 | : 3
x = 3

2 (13 - x) - 9 = 1
26 - 2x - 9 = 1
-2x + 17 = 1 | - 17
-2x = -16 | : (-2)
x = 8

3 (1 - x) + 2 = -7
3 - 3x + 2 = -7
5 - 3x = - 7 | -5
-3x = -12 | : (-3)
x = 4

3 (x + 3) = 2 (x + 4) + 1 + x
3x + 9 = 2x + 4 + 1 + x
3x + 9 = 3x + 5 | -3x - 9
0 = -4

4 (3x + 2) + 5 (2x + 3) = - (2x + 13)
12x+ 8 + 10x + 15 = -2x - 13
22x + 23 = -2x - 13 | +2x - 23
24x = -33 | : 24
x = -33/24

4 (x - 2) - 2 (x - 4) = 5(x + 1) - 3x
4x - 8 - 2x + 8 = 5x + 5 - 3x
2x = 2x + 5
0 = 5

2 (x - 4) = 2 (2x - 1) + 6 (x + 1)
2x - 8 = 4x - 2 + 6x + 6
2x - 8 = 10x + 4 | - 10x + 8
-8x = 12 | : (-8)
x = -12/8

0,2x + 0,3 = 1,3 | * 10
2x + 3 = 13 | - 3
2x = 10 | :2
x = 2

5x - 0,8 = 0,1 + 2x | * 10
50x - 8 = 1 + 20x | - 20x + 8
30x = 9 | : 30
x = 9/30


½y + 3 = 7 | * 2
y + 6 = 14 | - 6
y = 8

0,6y + 0,4y = 4 | * 10
6y + 4y = 40
10y = 40 | : 10
y = 4